Effectiveness of Turmeric (Curcumin Longa L) Against CRP and IL-6: Literature Review - Eka Nur Maulidya; Irna Diyana Kartika; Abdi Dwiyanto (Journal La Medihealtico, 2026)
Inflammation is a biological response to infection, injury, or tissue damage and is commonly marked by increased inflammatory biomarkers, including C-Reactive Protein (CRP) and Interleukin-6 (IL-6). Turmeric (Curcuma longa L.), particularly its active compound curcumin, has been widely studied for its anti-inflammatory potential through the inhibition of nuclear factor-kappa B (NF-κB), cyclooxygenase-2 (COX-2), and pro-inflammatory cytokines. This study aimed to review the effectiveness of turmeric/curcumin in reducing CRP and IL-6 levels based on previously published studies. This research used a narrative literature review design by collecting relevant articles from Google Scholar, Semantic Scholar, PubMed NCBI, and ResearchGate. The inclusion criteria consisted of full-text articles published between 2021 and 2026, written in Indonesian or English, and discussing the effect of turmeric or curcumin on CRP and/or IL-6. A total of 10 articles were reviewed and analyzed descriptively. The findings showed that turmeric/curcumin supplementation generally demonstrated anti-inflammatory effects, particularly in reducing CRP levels. Several studies also reported significant reductions in IL-6, especially in chronic inflammatory conditions such as type 2 diabetes mellitus, asthma, and other metabolic disorders. However, the effectiveness of curcumin on IL-6 remained inconsistent across different clinical conditions, including chronic kidney disease, rheumatoid arthritis, and systemic lupus erythematosus. These variations may be influenced by dosage, duration of supplementation, disease severity, sample characteristics, and curcumin bioavailability. In conclusion, turmeric/curcumin has potential as an adjunctive anti-inflammatory therapy, particularly for reducing CRP levels, while its effect on IL-6 requires further confirmation through well-designed clinical studies with larger sample sizes and standardized formulations.